Vaccination as a preventative measure contributing to immune fitness - Béatrice Laupèze (Nature Portfolio, 2021)
Abstract The primary goal of vaccination is the prevention of pathogen-specific infection. The indirect consequences may include maintenance of homeostasis through prevention of infection-induced complications; trained immunity that re-programs innate cells to respond more efficiently to later, unrelated threats; slowing or reversing immune senescence by altering the epigenetic clock, and leveraging the pool of memory B and T cells to improve responses to new infections. Vaccines may exploit the plasticity of the immune system to drive longer-term immune responses that promote health at a broader level than just the prevention of single, specific infections. In this perspective, we discuss the concept of “immune fitness” and how to potentially build a resilient immune system that could contribute to better health. We argue that vaccines may contribute positively to immune fitness in ways that are only beginning to be understood, and that life-course vaccination is a fundamental tool for achieving healthy aging.